EP492 Comparison between laparoscopic and robotic surgery, for sentinel lymph node mapping in endometrial cancer using indocyanine green and near infra-red fluorescence imaging. (1st November 2019) - Chaowawanit, W; Campbell, V; Wilson, E; Chetty, N; Perrin, L; Jagasia, N; Barry, S
Abstract : Introduction/Background: Indocyanine green (ICG) and near infra-red fluorescence imaging is used in both laparoscopic and robotic surgery to map the sentinel lymph node (SLN). The aim of this study is to compare the outcomes of sentinel lymph node (SLN) mapping between laparoscopic and robotic surgery. Methodology: One hundred and twenty women with histologically confirmed endometrial cancer, treated with a minimally invasive hysterectomy, bilateral salpingo-oophorectomy and SLN mapping were included. After anaesthetic induction, ICG was superficially injected (2–3 mm) into cervical submucosa and deeply injected into cervical stroma at the 3 and 9 o'clock positions on the cervix (1 ml or 1.25 mg per site). Results: Eleven cases were abandoned after ICG injection (laparoscopic surgery 7 cases and robotic surgery 4 cases) because of obesity, technical difficulty and peritoneal disease. One hundred and nine patients were analyzed. Seventy-six patients (70%) had a laparoscopic procedure and 33 patients (30%) had robotic surgery. The overall and bilateral detection rates were 97% and 83% for laparoscopic surgery and 88% and 73% for robotic surgery. Laparoscopic surgery was superior to robotic surgery in terms of overall detection (p-value 0.046). There was no significant difference in the intra-operative SLN identification time or SLN dissection time between laparoscopy and robotic surgery. Conclusion: Further research is required to compared laparoscopy and robotic surgery in terms of SLN detection. Disclosure: Nothing to disclose.